Formação agroindustrial do Oeste de Santa Catarina: infraestruturas como processos de desenvolvimento regional - Zanella, Ana Paula (2018)
The present thesis discusses the process of occupation and agro-industrial formation in the west region of Santa Catarina, since its initial formation by small market producers, up to the new market structures, through its insertion in the spatial production circuit. Demonstrating still that, in each historic moment the production originates the arrival of new logistic means. And so, as these agroindustries expanded, they received State apparatus for this growth, with the modernization, technological learning and infrastructure needed for expansion. Consequently, structuring and being incorporated into the national and international markets.